PENDAMPINGAN KEPADA PAGUYUBAN PEDAGANG PELATARAN PASAR KLEWER (P4K) SURAKARTA TENTANG KETERTIBAN LINGKUNGAN - Nurati, Dian Esti (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2018)
unorganized street sellers is sufficiently significant. The data existing in Trade Service shows out of 5,817 street sellers registered, some of them have not been arranged completely by Surakarta City Government. New Klewer Market opened officially on April 21, 2017 by Trade Service can arrange the placement of sellers better in New Klewer Market. Process of validating Klewer Market’s seller data completed by City Government indicates that 2,211 sellers will be arranged and placed, passing through a procedure including registering, problem mapping, scheduling, and requirement communicated to all sellers. Similarly, the Street Sellers affiliated with Klewer Market Yard Sellers Association (Paguyuban Pedagang Pelataran Pasar Klewer, thereafter called P4K) have been arranged on the fourth floor of new Klewer Market building, consisting of more than 900 sellers. All yard sellers should know environment orderliness organized by management and should comply with it. The problems faced by the sellers not permitted to transfer their shanties to others have been apparently understood by sellers. City Government attempted to establish more intensive and better communication, in socializing the rules to the sellers. Cooperation between City Government and organizers and sellers to maintain the environmental orderliness in Klewer Market is expected to implement the arrangement of Yard Sellers in Klewer Market of Surakarta corresponding to the arrangement program. The yard seller arrangement policy in Klewer Market of Surakarta referring to the good application of cooperation can realize better the performance of Surakarta City Government, in this case Trade Service of Surakarta City.Keywords: management and arrangement, environmental orderliness understanding, Klewer Market’s Street Sellers